The emerging role of Fusobacteria in carcinogenesis - Gibbs, Raisha J.; Chambers, Adam C.; Hill, Darryl J. (European journal of clinical investigation, 2024)
The Fusobacterium genus comprises Gram‐negative, obligate anaerobic bacteria that typically reside in the periodontium of the oral cavity, gastrointestinal tract, and female genital tract. The association of Fusobacterial spp. with colorectal tumours is widely accepted, with further evidence that this pathogen may also be implicated in the development of other malignancies. Fusobacterial spp. influence malignant cell behaviours and the tumour microenvironment in various ways, which can be related to the multiple surface adhesins expressed. These adhesins include Fap2 (fibroblast‐activated protein 2), CpbF (CEACAM binding protein of Fusobacteria), FadA (Fusobacterium adhesin A) and FomA (Fusobacterial outer membrane protein A). This review outlines the influence of Fusobacteria in promoting cancer initiation and progression, impacts of therapeutic outcomes and discusses potential therapeutic interventions where appropriate.